Electronic structure and superconductivity of single-layer FeSe on Nb:SrTiO3/LaAlO3 with varied tensile strain. (4th February 2016) - Huang, Z C; Pu, Y J; Xu, H C; Xu, D F; Song, Q; Lou, X; Wen, C H P; Peng, R; Feng, D L
Abstract: To understand the high temperature superconductivity at 65 K in single-layer FeSe films grown on Nb:SrTiO3 substrates, one crucial issue is to distinguish the effects of different interfacial interactions. In this paper, we decouple the effect of tensile strain with those of other interfacial interactions, and studying the corresponding electronic structure and superconducting gap behavior through in - situ angle resolved photoemission spectroscopy. By growing single-layer FeSe/Nb:SrTiO3 /LaAlO3 heterostructures with varied thicknesses of Nb:SrTiO3 films, the tensile strain on FeSe is controlled from 0.6% to 3.7% while preserving other interfacial interactions as in single-layer FeSe grown on Nb:SrTiO3 substrate. The electronic correlation strength is weakened with reduced tensile strain. The superconducting transition temperature ( T c ) is positively correlated with the tensile strain in single-layer FeSe/Nb:SrTiO3 when the film morphology is well ordered. Remarkably, the T c remains 55 K in single-layer FeSe with negligible tensile strain. These results help to reveal the effect of tensile strain on the enhanced superconductivity in single-layer FeSe/Nb:SrTiO3 .